Modeling correlated discrete uncertainties in event trees with copulas - Wang, Tianyang, author; Dyer, James S., author; Butler, John C., author; Risk Analysis, publisher (Colorado State University. Libraries, 2015)
Modeling the dependence between uncertainties in decision and risk analyses is an important part of the problem structuring process. We focus on situations where correlated uncertainties are discrete, and extend the concept of the copula‐based approach for modeling correlated continuous uncertainties to the representation of correlated discrete uncertainties. This approach reduces the required number of probability assessments significantly compared to approaches requiring direct estimates of conditional probabilities. It also allows the use of multiple dependence measures, including product moment correlation, rank order correlation and tail dependence, and parametric families of copulas such as normal copulas, t‐copulas, and Archimedean copulas. This approach can be extended to model the dependence between discrete and continuous uncertainties in the same event tree.
Published as: Risk Analysis, vol. 36, no. 2, February 2016, pp. 396–410. https://doi.org/10.1111/risa.12451.
Keywords: copulas; decision analysis; dependence; discrete uncertainties; event trees; probabilistic risk analysis